Legal Justice for Revenge Porn Victims: Rethinking Indonesia's Cyber Law from a Victim-Centered Perspective - Nabila Ayuningtyas; Subekti Subekti; Rehnalemken Ginting; Supanto Supanto (CV. Dyoqu Publishing and Management, 2025)
Background: The dissemination of intimate content without consent, commonly known as revenge porn, has emerged as a serious form of cybersexual violence in the digital era. The perpetrators often use social media platforms to spread such content as a form of retaliation. This issue poses significant psychological, emotional, and social harm to victims, exacerbated by the lack of specific legal safeguards in Indonesia. Aims: This study seeks to explore the urgency of legal protection for individuals affected by revenge porn and assess the extent to which current Indonesian legislation provides such protection. Methods: Using a normative-empirical legal research method with both descriptive and futuristic approaches, this study collected data through literature analysis and interviews with law enforcement and victim support organizations. The data were analyzed through qualitative interpretation. Result: The study found that legal mechanisms to support victims of revenge porn are still highly inadequate. Existing laws, such as the Pornography Law and the Electronic Information and Transactions Law, lack specific provisions and may even criminalize the victims. Although institutions like the Witness and Victim Protection Agency (LPSK) exist, access to protection is limited and dependent on formal requests. Additionally, personal data protection remains underregulated. Conclusion: There is a pressing need for a more inclusive legal framework that offers specific protection for victims of digital sexual violence. The development and enactment of new legal instruments, such as the Sexual Violence Eradication Bill and the Personal Data Protection Bill, are essential to ensure justice and restore dignity for those affected by revenge porn.